Viabilidade do cultivo de soja irrigada por pivô central em uma propriedade de Dom Pedrito/RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Currently seasonality in climate behavior that occurs in the Campaign Region of Rio Grande do Sul, mainly rainfall changes, has become increasingly troubling in the agricultural sector; distribution of rainfall during the summer; the use of irrigation has become a guarantee of good results in production. With concern increasing market demand, soy is an alternative guaranteed profitability for the producer with the use of irrigation. So this paper aims to study the feasibility of implementing an irrigation system center pivot under soybean cultivation, the study was conducted in the property located in Dom Pedrito / RS. The referenced data were collected through an interview and data analysis of the property. It was designed to an analysis of data from harvests of 2017/2018 with the soybean crop irrigated by center pivot, noting also within this period distributions of rainfall. In the result we have seen that it is possible and very profitable for the producer of soybean cultivation irrigated, 122,15% earning more in total production with the use of irrigation.
Keywords: Pivô; Produção de soja; Região da campanha; Pivot; Soybean production; Campaign Region; CNPQ::CIENCIAS AGRARIAS